2017
DOI: 10.18632/oncotarget.23641
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes define distinct subgroups of salivary gland adenoid cystic carcinoma with different driver mutations and outcomes

Abstract: The relative rarity of salivary gland adenoid cystic carcinoma (ACC) and its slow growing yet aggressive nature has complicated the development of molecular markers for patient stratification. To analyze molecular differences linked to the protracted disease course of ACC and metastases that form 5 or more years after diagnosis, detailed RNA-sequencing (RNA-seq) analysis was performed on 68 ACC tumor samples, starting with archived, formalin-fixed paraffin-embedded (FFPE) samples up to 25 years old, so that cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 65 publications
4
44
0
Order By: Relevance
“…Transcriptional regulation of the MYB gene has not been studied in detail in ACC tumors, but in most tissues and tumor types, transcription of the gene initiates upstream of exon 1 at the normal promoter, designated here as TSS1 (Transcription Start Site 1, Figure 1A) [12,13]. Detailed analyses of RNA-sequencing (RNA-seq) studies of ACC tumors [7,8] have revealed that nearly all ACC tumors have very few reads aligned to the first exon of the MYB gene, suggesting an anomaly in its transcriptional regulation in ACC. In addition to the normal TSS1 promoter, several additional regulatory elements have been described in the MYB gene.…”
Section: Acc Tumors Utilize Two Myb Gene Promotersmentioning
confidence: 99%
See 3 more Smart Citations
“…Transcriptional regulation of the MYB gene has not been studied in detail in ACC tumors, but in most tissues and tumor types, transcription of the gene initiates upstream of exon 1 at the normal promoter, designated here as TSS1 (Transcription Start Site 1, Figure 1A) [12,13]. Detailed analyses of RNA-sequencing (RNA-seq) studies of ACC tumors [7,8] have revealed that nearly all ACC tumors have very few reads aligned to the first exon of the MYB gene, suggesting an anomaly in its transcriptional regulation in ACC. In addition to the normal TSS1 promoter, several additional regulatory elements have been described in the MYB gene.…”
Section: Acc Tumors Utilize Two Myb Gene Promotersmentioning
confidence: 99%
“…In addition, an infrequently used alternative promoter, designated here as TSS2, is located just upstream of exon 2 ( Figure 1A) [18,19]. We visually inspected the RNA-seq reads from two frozen ACC tumors (T73 and T9; clinical information [7]). Figure 1A shows a genome browser view of the RNA-seq coverage of the first four exons of the MYB gene.…”
Section: Acc Tumors Utilize Two Myb Gene Promotersmentioning
confidence: 99%
See 2 more Smart Citations
“…18). However, in contrast to studies on gene expression of ACC, no difference in outcome was identified between these two groups (240). Although the survival curve of Group 1 had a somewhat steeper decline than that of Group 2, it remains speculative whether additional cases would have revealed a difference.…”
Section: Primary and Metastatic Adenoid Cystic Carcinoma Of The Salivmentioning
confidence: 68%